Clustering of metabolic comorbidity in schizophrenia: a genetic contribution? - Gough, S; O'Donovan, M (2005)
People with schizophrenia are more likely to develop type 2 diabetes than the general population. Although an increased risk of diabetes has been attributed to environmental determinants such as diet, lifestyle and antipsychotic drugs, the association between these two disorders was noticed well before the advent of current lifestyles and pharmacological interventions, raising the possibility of a shared genetic basis. Schizophrenia and type 2 diabetes are common diseases with a complex mode of inheritance which includes both genetic factors and environmental determinants. As susceptibility genes for both type 2 diabetes and schizophrenia are beginning to be identified there is increasing interest in the possibility of shared susceptibility loci between the two conditions. This article reviews the genetic basis to schizophrenia and type 2 diabetes and discusses the potential for shared loci between both conditions.